Teachers' Views On Students' Performance In English Language Proficiency Courses Via Cefr Descriptors - Ramiaida Darmi; Noor Saazai Mat Saad; Norhana Abdullah; Fariza Puteh-Behak; Zarina Ashikin Zakaria; Juliana Niza Ismail Adnan (OCERINT International Organization Center of Acade, 2024)
‘The English Language Education in Malaysia: An Agenda for Reform 2015-2025’ is a blueprint initiated by The Ministry of Education (MOE), Malaysia, currently launched in 2016. The key pledge to this blueprint is the alignment of Malaysia’s English Language Education System with the Common European Framework of Reference for Languages (CEFR). CEFR is a benchmark for an international standard that focuses on developing learners who are able to communicate and interact in any language, in this instance, English. The focal point of the Malaysian education reform is to adopt the CEFR levels as the guiding beacon or regulating framework for curriculum development, issues regarding learning materials and the measurement of learning outcomes. In keeping with this reform, the study aims to understand English language teachers’ views on the English language proficiency courses in a local university, in Malaysia, based on CEFR scales. The study employs a quantitative approach, where surveys were distributed to twenty-five English language teachers. The data is then analysed quantitatively by frequency counts and percentage. Data shows there are variations in teachers’ views towards English language proficiency courses, and this may not necessarily fit into the CEFR standards targeted for university learners. The result of this study acts as preliminary data for further research on the link between English language course content and CEFR standards, as well as expected English language proficiency of university learners. Through this study, it is hoped that future design of teaching and learning materials that contribute to ‘proficient’ learners at the end of university years, can be developed.